2022
DOI: 10.7554/elife.76721
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc plays a key role in IFN-γ-induced persistence of Chlamydia trachomatis

Abstract: Chlamydia trachomatis (Ctr) can persist over extended times within their host cell and thereby establish chronic infections. One of the major inducers of chlamydial persistence is interferon-gamma (IFN-γ) released by immune cells as a mechanism of immune defence. IFN-γ activates the catabolic depletion of L-tryptophan (Trp) via indoleamine-2,3-dioxygenase (IDO), resulting in persistent Ctr. Here, we show that IFN-γ induces the downregulation of c-Myc, the key regulator of host cell metabolism, in a STAT1-depen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…HPV/CT co-infected women had a higher microbial diversity, Aerococcus christensenii was associated with C. trachomatis infection. addition to tryptophan depletion, a recent study found that IFN-g also can down regulate c-Myc, the key regulator of host cell metabolism, resulting in the reduction of TCA cycle intermediates and nucleotides to prevent chlamydial replication and promoting persistence (Rajeeve et al, 2020;Vollmuth et al, 2022). Constitutive expression of c-Myc can rescue CT from persistence induced by IFN-g. Dong et al (Dong et al, 2022) proved that the abundance of Prevotella correlates with the expression of cervical TLR4, NF-kB, C-myc, and hTERT genes.…”
Section: The Effect Of Cervicovaginal Microbiota On Sti Infection Ct ...mentioning
confidence: 99%
“…HPV/CT co-infected women had a higher microbial diversity, Aerococcus christensenii was associated with C. trachomatis infection. addition to tryptophan depletion, a recent study found that IFN-g also can down regulate c-Myc, the key regulator of host cell metabolism, resulting in the reduction of TCA cycle intermediates and nucleotides to prevent chlamydial replication and promoting persistence (Rajeeve et al, 2020;Vollmuth et al, 2022). Constitutive expression of c-Myc can rescue CT from persistence induced by IFN-g. Dong et al (Dong et al, 2022) proved that the abundance of Prevotella correlates with the expression of cervical TLR4, NF-kB, C-myc, and hTERT genes.…”
Section: The Effect Of Cervicovaginal Microbiota On Sti Infection Ct ...mentioning
confidence: 99%
“…Most recent studies suggest that IFNγ-induced persistence in Chlamydiae is not induced by the activity of IDO, but rather by host cell transcription factor c-Myc [ 39 ]. c-Myc is a major polyvalent regulator of cell growth and proliferation and is essential for successful C. trachomatis infection.…”
Section: The Metabolic Shutdown Induced By Tryptophan Depletion Is Pa...mentioning
confidence: 99%
“…Upon IFNγ stress, c-Myc levels are depleted concomitantly with TCA cycle intermediary products, leading to chlamydial persistence. Persistence could be rescued with over-expression of c-Myc or by adding TCA intermediates despite the ongoing stress, in cell cultures as well as in organoids derived from human fallopian tubes [ 39 ].…”
Section: The Metabolic Shutdown Induced By Tryptophan Depletion Is Pa...mentioning
confidence: 99%
See 2 more Smart Citations